HIGH 5 STRATEGIES AS AN ALTERNATIVE TEACHING STRATEGY IN EFL CLASSROOM - Desi Surayatika (Global Expert: Jurnal Bahasa dan Sastra, 2014)
This study describes the use of High 5 Strategies in English Foreign Language classroom. As one of teaching strategies, High 5 strategies can help the students to tackle their reading. High 5 strategies consists of activating background knowledge, questioning, analyzing text structure, creating mental images, and summarizing. First, activating background knowledge is the important concept of reading that can help the students to connect what they already learned or knew before so that it allows the students to get a better understanding of what it is about. Second, question is also the important way for students to form questions that help them understand what to look for as they read. Then, the students need to understand the structure of the text that help them easier comprehend each part of paragraph in the text by analyzing the text structure. Next, creating mental image or visualizing is used to imagine the structure of the text that the students have known before, so as they read, they should also imagine how the structure is. Finally, the students summarize all important information that they already got using the previous strategies. High 5 strategies provide an opportunity for all the EFL students to activate their background knowledge and form question in their mind, analyze, visualize and summarize the reading. In short, High 5 strategies can be used to help the students to learn better especially in improving their reading skill.